Zero-delay FPGA-based odd-even sorting network - Hematian, Amirshahram (2013)
Abstract: Sorting is one of the most well-known problems in computer science and is frequently used for benchmarking computer systems. It can contribute significantly to the overall execution time of a process in a computer system. Dedicated sorting architectures can be used to accelerate applications and/or to reduce energy consumption. In this paper, we propose an efficient sorting network aiming at accelerating the sorting operation in FPGA-based embedded systems. The proposed sorting network is implemented based on an Optimized Odd-even sorting method (O2) using fully pipelined combinational logic architecture and ring shape processing. Consequently, O2 generates the sorted array of numbers in parallel when the input array of numbers is given, without any delay or lag. Unlike conventional sorting networks, O2 sorting network does not need memory to hold data and information about sorting, and neither need input clock to perform the sorting operations sequentially. We conclude that by using O2 in FPGA-based image processing, we can optimize the performance of filters such as median filter which demands high performance sorting operations for realtime applications.